Relación entre la q de Tobin y el apalancamiento de veintidós empresas emisoras de la bolsa de valores de Colombia en el periodo 2004 - 2012 (2018)
This paper presents the development of a research on the relationship between Tobin's q ratio and the leverage of twenty-two issuing companies of the Colombian stock exchange for the period 2004 to 2012. Where the Tobin's q ratio being greater than 1 indicates that the market value at book value is high, which means that the investment will be stimulated, but obtaining resources from the stock market which would be favorable instead of the use of financing through debt. The econometric exercise results in the non-rejection of the null hypothesis except for three companies that reject the hypothesis, it is identified that there is indeed a relationship between the variables that can be caused in both directions, however, a latent need for include a series of additional financial indexes, both traditional and intangible, in order to explain the model robustly, such as the index of corporate governance, which can be an important variable to make financial decisions